2016
DOI: 10.1016/j.arr.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal cathepsins and their regulation in aging and neurodegeneration

Abstract: Lysosomes and lysosomal hydrolases, including the cathepsins, have been shown to change their properties with aging brain a long time ago, although their function was not really understood. The first biochemical and clinical studies were followed by a major expansion in the last 20 years with the development of animal disease models and new approaches leading to a major advancement of understanding of the role of physiological and degenerative processes in the brain at the molecular level. This includes the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
238
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(257 citation statements)
references
References 257 publications
9
238
1
9
Order By: Relevance
“…Previous research revealed enhanced [51, 59] as well reduced lysosomal enzyme activities [38, 39] in various Grn −/− cells types or tissue. Based on our findings, these discrepancies may be explained by different cell types analyzed, difficulties with the determination of specific activities of lysosomal enzymes due to their complex proteolytic processing and consequences for their proteolytic activity [53, 61]. Single chain variants as well as dimeric variants of heavy and light chain are catalytically active whereas separated heavy and light chains are inactive [53, 61].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed enhanced [51, 59] as well reduced lysosomal enzyme activities [38, 39] in various Grn −/− cells types or tissue. Based on our findings, these discrepancies may be explained by different cell types analyzed, difficulties with the determination of specific activities of lysosomal enzymes due to their complex proteolytic processing and consequences for their proteolytic activity [53, 61]. Single chain variants as well as dimeric variants of heavy and light chain are catalytically active whereas separated heavy and light chains are inactive [53, 61].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to design a powerful and specific Cathepsin inhibitor, it is of fundamental importance to have detailed knowledge of the features of each sub-site of each Cathepsin [37][38][39]. In addition, it is worth highlighting that this class of enzyme is related to several pathological processes such as osteoporosis (Cathepsin K) [40,41], neurodegenerative disease (Cathepsin D) [42] and metastasis in several types of cancer (Cathepsins B, K, L and S) [43][44][45]. Hence, Cathepsins are promising targets for the treatment of such disorders [46].…”
Section: Decane (1) (3e)-2-chloro-3-(chloromethylidene)-2-(4-methoxymentioning
confidence: 99%
“…Elevated protease expression was found to be associated with poor patient prognosis across numerous tumor types (29). Other studies demonstrated important roles of lysosomal cysteine cathepsins in aging and neurodegeneration (30). Last but not least, cysteine cathepsins were reported to trigger caspase-dependent cell death through cleavage of BID (BH3 interacting-domain death agonist) and antiapoptotic Bcl-2 (B-cell lymphoma 2) homologs (31).…”
Section: Discussionmentioning
confidence: 99%